2021
DOI: 10.3389/fmolb.2021.708127
|View full text |Cite
|
Sign up to set email alerts
|

Glucotoxicity Activation of IL6 and IL11 and Subsequent Induction of Fibrosis May Be Involved in the Pathogenesis of Islet Dysfunction

Abstract: Background: Islet dysfunction is the main pathological process of type 2 diabetes mellitus (T2DM). Fibrosis causes islet dysfunction, but the current mechanism is still unclear. Here, bioinformatics analysis identified gene clusters closely related to T2DM and differentially expressed genes related to fibrosis, and animal models verified the roles of these genes.Methods: Human islet transcriptomic datasets were obtained from the Gene Expression Omnibus (GEO), and weighted gene coexpression network analysis (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The NECTIN2 cell adhesion molecule has been shown to participate in lipid metabolism and serves as a potential biomarker for disease progression in carotid artery stenosis (31). Additionally, the cytokines IL6 and IL11 are upregulated under glucotoxic conditions, and IL6/IL11-mediated islet fibrosis may contribute to dysfunction in T2DM (32). Furthermore, the BPI-like proteins LBP and BPI are involved in lipid homeostasis and have been implicated in cardiovascular pathogenesis (19).…”
Section: Discussionmentioning
confidence: 99%
“…The NECTIN2 cell adhesion molecule has been shown to participate in lipid metabolism and serves as a potential biomarker for disease progression in carotid artery stenosis (31). Additionally, the cytokines IL6 and IL11 are upregulated under glucotoxic conditions, and IL6/IL11-mediated islet fibrosis may contribute to dysfunction in T2DM (32). Furthermore, the BPI-like proteins LBP and BPI are involved in lipid homeostasis and have been implicated in cardiovascular pathogenesis (19).…”
Section: Discussionmentioning
confidence: 99%
“…In advanced T2DM patients, the abnormal buildup of ECM, known as fibrosis, is frequently observed and may contribute to organ malfunction [41]. Research involving bioinformatics analysis and animal models has revealed that high glucose levels could trigger the upregulation of IL11, leading to inflammation and fibrosis in islets, thus contributing to the development of islet dysfunction in T2DM [42]. Similarly, renal fibrosis is a common occurrence in various kidney diseases, which can lead to mechanical and electrical dysfunction and the progression of kidney dysfunction [40].…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression network was constructed using the “WGCNA” package (version 1.71) in R software (version 4.1.2) with the top 5000 genes with the highest median absolute deviation [ 50 , 51 ]. We constructed the adjacency matrix with an appropriate soft threshold (β = 6) when R 2 reached 0.85 after calculating the Pearson correlation coefficient between any two genes in the matrix.…”
Section: Methodsmentioning
confidence: 99%